‘Our People’ Telemovies, bangsa and nationalism 3.0 in Sabah, Malaysia (2012)
A thousand miles across the South China Sea from West or Peninsular Malaysia, the state of Sabah in the East enjoys a thriving telemovie industry that exists independently from filmmaking on the Peninsular side. Sold in the markets in video-CD format rather than made for television, homegrown telemovies made in Malay and local languages and dealing with local issues have become a highly popular entertainment medium in urban and rural Sabah ever since Orang Kita (Our People), the first to be made, was released in 2002. Orang Kita was a runaway success in Sabah, where it was most popular. It sold an impressive 35,000 copies and triggered a whole series of new titles released over the years (Abu Bakar Ellah 2009). Approximately forty to fifty telemovies have been produced to date, thirty of which by Skyline/Skylaser Enterprise, Sabah’s biggest telemovie production company. Aside from Orang Kita, popular titles include Orang Kita 2 (2006), PTI: Percintaan Tanpa Izin (Love Without Permission; 2005), and PTI 2 (2008). The telemovie explosion in Sabah has also increased the popularity of local celebrities such as Abu Bakar Ellah, Mat Kongo and Ela Sabah who are almost household names in the state. Sabah’s telemovies have relatively straightforward storylines. All are made on tight budgets and rely on small casts and limited equipment and technol - ogies. In terms of production value, they are discernibly much less polished than telemovies made for terrestrial or cable television, including Malay telemovies aired on Malaysian channels. In PTI, for instance, viewers can even spot the cardioid microphone peeking out from the top of the screen to capture dialogues between characters; while in Orang Kita, toilet humour frowned upon by the highbrow is used liberally. Such production shortcomings do not, however, detract from the value of local telemovies as appreciated by at least a majority of the target audience, namely the general populace of Sabah, encompassing the indigenous groups (such as the Kadazandusun, Murut and Bajau), the Malay and Chinese, as well as (illegal and legal) immigrants, especially from the Philippines. Clearly, for these viewers, the attraction of Sabah’s telemovies does not rest solely on standard production values; other variables matter too, including their regard for participatory values, social integration, diversity, truth-telling and fairness (Mulgan 1990).